1982
DOI: 10.1111/j.1469-8986.1982.tb02536.x
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory Evoked Potential Changes With a Selective Attention Task

Abstract: Somatosensory evoked potential (SEP) changes associated with selective attention were investigated. In 16 subjects, SEPs were recorded from five locations while they counted electrical stimuli to one of four randomly stimulated fingers. Sequential SEP events measured included peaks P30 (positivity at 30 msec). P45, N60, P100. N140. P190. N230, P400. Counting was associated with greater P45, P100. P190, N230, and P400 amplitudes; effects were not attributable to eye or tongue activity. Analyses designed to reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(36 citation statements)
references
References 22 publications
5
31
0
Order By: Relevance
“…The modulatory pattern of pain on tactile processing with a facilitation of later but not the earliest stages of tactile processing closely resembles attentional effects on tactile processing in somatosensory cortices as revealed by EEG (Desmedt and Tomberg 1989;Eimer and Forster 2003;Josiassen et al 1982;Michie et al 1987) and MEG (Mima et al 1998) recordings. These studies showed that focusing attention on a behaviorally relevant tactile stimulus facilitates S1 and S2 responses to tactile stimuli at latencies of 40 ms and later but do not modulate earliest S1 responses with latencies shorter than 40 ms.…”
Section: Discussionsupporting
confidence: 56%
“…The modulatory pattern of pain on tactile processing with a facilitation of later but not the earliest stages of tactile processing closely resembles attentional effects on tactile processing in somatosensory cortices as revealed by EEG (Desmedt and Tomberg 1989;Eimer and Forster 2003;Josiassen et al 1982;Michie et al 1987) and MEG (Mima et al 1998) recordings. These studies showed that focusing attention on a behaviorally relevant tactile stimulus facilitates S1 and S2 responses to tactile stimuli at latencies of 40 ms and later but do not modulate earliest S1 responses with latencies shorter than 40 ms.…”
Section: Discussionsupporting
confidence: 56%
“…Attentional effects at the latency of our later component have also been found: there is evidence that brain activity during this later time period reflects relatively complex aspects of tactile processing, e.g. these components are classically modulated by attention (Desmedt and Robertson, 1977;Josiassen et al, 1982;Garcia-Larrea et al, 1995;Mima et al, 1998). There is also evidence that mid-latency components are also dependent on conscious awareness (Schubert et al, 2006): in a study of backward masking the P100 and N140 SEP components had larger amplitude when the tactile targets were consciously perceived.…”
Section: Attentional Modulationmentioning
confidence: 62%
“…Some previous SEP studies have shown that relatively early SEP components (e.g. P27, P50) are modulated by attention (Josiassen et al, 1982;Seitz and Roland, 1992;Kunde and Treede, 1993;Mima et al, 1998) and one study (Legon and Staines, 2006) showed modulation of the N20 (to medial nerve stimulation) when attention to a tactile stimulus is needed to guide a motor task. Other studies have failed to find early attention effects (Desmedt and Robertson, 1977;Zopf et al, 2004).…”
Section: Attentional Modulationmentioning
confidence: 98%
“…Thus, P45 amplitude increases significantly when attention is actively directed to the stimulated hand [Desmedt et al, 1983;Josiassen et al, 1982], whereas drowsiness and sleep have depressing effects on P45 amplitude [Noguchi et al, 1995] leading to amplitude decreases down to levels near background noise. This might explain why P45 was virtually non identifiable in two of our subjects who became drowsy during the recordings.…”
Section: Spatial Discrimination Based On N20/p20 or P45 Sep Componentsmentioning
confidence: 95%